Predicting the price movement from candlestick charts: a CNN-based approach. (17th June 2020) - Hung, Chih-Chieh; Chen, Ying-Ju; Guo, Siou Jhih; Hsu, Fu-Chun
Candlestick charts have been widely used to display price movements of a security, derivative, or currency for a specific period. They are one type of popular charts for day traders. Motivated by the conventional use of candlestick charts as a visual aid for decision making in stock, currency exchange, and commodity trading, we proposed a framework deep candlestick predictor (DCP) to forecast the price movements by reading the candlestick charts instead of reading the considerable body of numerical data from financial reports. DCP consists of three components: 1) chart decomposer: decomposes a given candlestick chart into several sub-charts; 2) CNN-autoencoder: derives the best representation of sub-charts; 3) 1D-CNN: forecasts the price movements. An extensive study is conducted by daily prices from Taiwan Exchange Capitalization Weighted Stock Index which contains 21, 819 trading days. The result shows that DCP effectively achieves higher accuracy comparing to accuracy using conventional index-based models.